Serine proteinases from Bothrops snake venom activates PI3K/Akt mediated angiogenesis. (15th December 2016) - Bhat, Shreesha K.; Joshi, Manjunath B.; Ullah, Anwar; Masood, Rehana; Biligiri, Setlur G.; Arni, Raghuvir K.; Satyamoorthy, Kapaettu
Abstract: The discovery of rapid acting and powerful angiogenic proteins are of significant interest in the treatment of various human disorders associated with insufficient angiogenesis such as ischemia, menorrhagia and delayed wound healing. Snake venoms consist of a mixture of bioactive proteins and polypeptides and are rich sources of pharmacologically important molecules. Serine proteinases are one of the abundant proteins present in Bothrops snake venoms and possess multiple biological functions including the regulation of the blood coagulation cascade. In this study, serine proteinases from Bothrops atrox ( B. atrox ) and Bothrops brazili ( B. brazili ) that modulate angiogenesis were purified and characterized. Molecular size exclusion chromatography, affinity chromatography followed by ion exchange chromatography of the serine proteinases indicated molecular masses of around 32 kDa. Serine proteinases from both the species exhibited diverse catalytic activities such as the ability to induce amidolytic, fibrinogenolytic, gelatinolytic activities and also coagulated plasma with a minimal coagulation concentration of 2.4 μg/mL. Serine proteinases facilitated the sprouting of human umbilical vein endothelial cells (HUVEC) in three-dimensional culture systems and induced tubule formation in monolayer culture systems. Serine proteinase stimulated Akt ser473 and eNOS ser1177 phosphorylation in endothelial cells and addition of PI3K inhibitor LY294002 abrogated the effects of serine proteinases on sprout formation of endothelial cells in 3D collagen gels, suggesting that serine proteinase facilitated angiogenesis was mediated by PI3K/eNOS signaling axis. We also show in agarose plug assays using a mouse model, serine proteinases from Bothrops venoms significantly enhanced neovascularization. Our data suggests pro-angiogenic activity by the serine proteinases from B. atrox and B. brazili venom and further studies are warranted to explore the therapeutic applications. Highlights: Serine proteinases from Bothrops atrox and Bothrops brazili exhibits diverse activities. Serine proteinases induce angiogenesis in in vitro and in vivo systems. Serine proteinases activate the PI3K/Akt pathway.